Host miRNA-Mediated Lineage Control and HPV Transcriptional Regulation: Mechanistic Insights with Environmental Sustainability Perspectives - Nishant Kumar Singh,; Agrika Gupta,; Aashi Saldhi,; Arushi Chowdhary,; Prankur Awasthi,; Saba Hasan, (Public Health, 2026)
Viruses cause 10%–15% of human cancers worldwide. Genomic instability, including DNA damage and the accumulation of mutations and aberrations, is the most common outcome of virus-induced reprogramming. One of the most infectious viruses that causes cancer and spreads sexually is the human papillomavirus (HPV). Mostly HPV causes tumours of the cervix, head and neck, anus, penis, vulva, and vagina. Most HPV infections go away within the first two years. However, in some instances, the infection persists, and the lesions develop into cancerous cells. The E7 and E6 oncoproteins are required for cancer development in high-risk HPV (HR-HPV) types, particularly HPV 18 and HPV 16. Noncoding microRNAs (miRNAs) are involved in post-transcriptional regulation in cervical cancer, as they are in other tumours, resulting in abnormal expression profiles. The miRNAs are small, non-coding, single-stranded post-transcriptional units that play a significant role in the mentioned tumours as tumour suppressors and oncogenes. However, the systemic impact of HPV16 on miRNAs is still unknown. These interactions map potential pathways, allowing possible mechanistic links to be identified. Further, we have discussed the prophylactic vaccines, which are currently in use as a preventive measure, and various therapeutic vaccines are still being developed and under clinical trials. The review paper highlights the functions of various miRNAs in HPV-induced cancers, along with HPV epidemiology, genome structure, stages of pathogenesis, the role of miRNAs in cancers, and recent advances made in the field of therapeutics.